Introduction To Hijaiyah Letters With a Humanistic Approach in Grade 4 of MI Negeri Salatiga - Salma Ubaidah; Haikal Akhtar Haniff; Rina Asih Handayani (Jurnal Ilmiah Global Education, 2026)
This study aims to describe the application of a humanistic approach in learning the hijaiyah letters as an effort to introduce the hijaiyah letters to fourth-grade students of MI Negeri Salatiga. The background of this study begins with the problem of students' low ability to recognize and pronounce the hijaiyah letters correctly due to monotonous and teacher-centered learning methods. The humanistic approach was chosen because it emphasizes the emotional, spiritual, and intellectual needs of students and places students as the center of learning. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The research subjects included Arabic language teachers and fourth-grade students of MI Negeri Salatiga. The results of the study indicate that the application of a humanistic approach through interactive, contextual, and student-centered learning activities can improve students' hijaiyah reading skills, active participation, and learning motivation. The teacher acts as a facilitator, providing guidance and appreciation for each student's efforts.